The Genetic Diversity of Mesodinium and Associated Cryptophytes - Johnson, Matthew D.; Beaudoin, David J.; Laza-Martinez, Aitor; Dyhrman, Sonya T.; Fensin, Elizabeth; Lin, Senjie; Merculief, Aaron; Nagai, Satoshi; Pompeu, Mayza; Setälä, Outi; Stoecker, Diane K. (Frontiers in Microbiology, 2016)
Ciliates from the genus Mesodinium are globally distributed in marine and freshwater ecosystems and may possess either heterotrophic or mixotrophic nutritional modes. Members of the M. major/rubrum species complex photosynthesize by sequestering and maintaining organelles from cryptophyte prey, and under certain conditions form periodic or recurrent blooms (= red tides). Here we present an analysis of the genetic diversity of Mesodinium and cryptophyte populations from 10 environmental samples (8 globally dispersed habitats including 5 Mesodinium blooms), using group-specific primers for Mesodinium partial 18S, ITS, and partial 28S rRNA genes as well as cryptophyte large subunit RuBisCO genes (rbcL). In addition, 22 new cryptophyte and 4 new M. rubrum cultures were used to extract DNA and sequence rbcL and 18S-ITS-28S genes, respectively, in order to provide a stronger phylogenetic context for our environmental sequences. Bloom samples were analyzed from coastal Brazil, Chile, two Northeastern locations in the United States, and the Pribilof Islands within the Bering Sea. Additionally, samples were also analyzed from the Baltic and Barents Seas and coastal California under non-bloom conditions. Most blooms were dominated by a single Mesodinium genotype, with coastal Brazil and Chile blooms composed of M. major and the Eastern USA blooms dominated by M. rubrum variant B. Sequences from all 4 blooms were dominated by T. amphioxeia-like cryptophytes. Non-bloom communities revealed more diverse assemblages of Mesodinium spp., including heterotrophic species and the mixotrophic M. chamaeleon. Similarly, cryptophyte diversity was also higher in non-bloom samples. Our results confirm that Mesodinium blooms may be caused by M. major, as well as multiple variants of M. rubrum, and further implicate T. amphioxeia as the key cryptophyte species linked to these phenomena in temperate and subtropical regions.